Reading with a Simulated 60-Channel Implant - Perez Fornos, Angelica; Sommerhalder, Jörg R.; Pelizzone, Marco (Frontiers in Neuroscience, 2011)
First generation retinal prostheses containing 50-60 electrodes are currently in clinical trials. The purpose of this study was to evaluate the theoretical upper limit (best possible) reading performance attainable with a state-of-the-art 60-channel retinal implant and to find the optimum viewing conditions for the task. Four normal volunteers performed full-page text reading tasks with a low resolution, 60-pixel viewing window that was stabilized in the central visual field. Two parameters were systematically varied: (1) spatial resolution (image magnification) and (2) the orientation of the rectangular viewing window. Performance was measured in terms of reading accuracy (% of correctly read words) and reading rates (words/min). Maximum reading performances were reached at spatial resolutions between 3.6 and 6 pixels/char. Performance declined outside this range for all subjects. In optimum viewing conditions (4.5 pixels/char), subjects achieved almost perfect reading accuracy and mean reading rates of 26 words/min for the vertical viewing window and of 34 words/min for the horizontal viewing window. These results suggest that, theoretically, some reading abilities can be restored with actual state-of-the-art retinal implant prototypes if “image magnification” is within an “optimum range”. Future retinal implants providing higher pixel resolutions, thus allowing for a wider visual span might allow faster reading rates.